A Cross Sectional Study to Assess the Health Status of Priests in A Pilgrimage City of Central India - Sanjay Kumar Chourasiya; Arpit Verma; Anil Singh Baghel; Satish Saroshe (Medsci Publications, 2016)
Background: Priesthood demands some characteristic unique working environment i.e. mostly closed damped, smoky, noisy & crowded workplace. They are more prone accidents at workplace & are suppose to take high calorie diet in form of Prasad (everyday) & in religious ceremonies (occasionally).This lifestyle may affect their health status & give rise to various diseases. The objective of this study was to assess the health status & quality of life of priests serving in temples of Ujjain city. Method: Sample size was calculated with the help of formula n = 4pq/L2. A total of 440 priests were interviewed. As a study instrument, we used the generic questionnaire 36-item short form survey (SF-36). Results: Mean ages (SD) of study participants were found to be 41.6 (±17.6). Majority of study participants 264(60%) had excellent Physical functioning. Role play emotional was excellent in most of the study participant's 332 (74.5%). Conclusion: There is a high prevalence of Non communicable disease among the priest of the pilgrimage city of central India.